1993
DOI: 10.1103/physrevlett.71.3669
|View full text |Cite
|
Sign up to set email alerts
|

Real space observation of dynamic scaling in a critical polymer mixture

Abstract: We have studied the growth of the wetting layer formed at the surface of a critical mixture of poly (ethylene propylene) and perdeuterated poly (ethylene propylene) during spinodal decomposition. The wavelength of the surface spinodal wave is found to grow as t 1/3 over the entire range of times accessible in the experiment. The composition profiles exhibit universal scaling behavior in the near-surface region. These results are in excellent agreement with a recent numerical study on surface-directed spinodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
94
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 21 publications
11
94
2
Order By: Relevance
“…Experiments [4][5][6] and simulations 7,8 have shown that in SDSD, a composition wave normal to the film surface forms at the surface due to the preferential attraction of the surface to one of the two components. This wave then propagates into the film bulk and decays because of thermal noise.…”
Section: -8mentioning
confidence: 99%
“…Experiments [4][5][6] and simulations 7,8 have shown that in SDSD, a composition wave normal to the film surface forms at the surface due to the preferential attraction of the surface to one of the two components. This wave then propagates into the film bulk and decays because of thermal noise.…”
Section: -8mentioning
confidence: 99%
“…the alignment of phase domains with respect to the patterned substrate (accompanied by free surface undulations), is the second main issue [19] discussed here. Selfassembly of polymer blends, cast as thin films on both homogeneous as well as patterned substrates, is a consequence of surface-directed phase separation [1,3,4,[9][10][11][12][13][23][24][25][26][27][28][29][30][31][32], discovered [23,27] only 10 years ago and described shortly below. Molecular mobility in the phase-separating films is promoted by the temperature elevated above glass transition (temperature quench applied for partly miscible or immiscible mixtures) or a common solvent added to the polymer blend (solvent quench encountered commonly for immiscible blends).…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, it has been recognized that for thin-film geometry, SD may interact with wetting phenomena resulting in a very different structure at the surfaces compared to the bulk behavior. [4][5][6][7] This phenomenon has been called surfacedirected spinodal decomposition ͑SDSD͒. SDSD simulations show that a composition wave perpendicular to the surface forms at the surface due to the preferential attraction of the surface to one of the two components.…”
mentioning
confidence: 99%
“…Most experimental studies in SDSD have been carried out in polymer mixtures where a small self-diffusion coefficient slows the SD dynamics and the associated phase diagrams can be tailored. 4,5 While it is predicted that SD could occur generally in any two-component system whose phase diagram shows a miscibility gap, such as ZrO 2 As complementary metal oxide semiconductor ͑CMOS͒ technology progresses, scaling of the traditional gate dielectrics, i.e., SiO 2 and SiO x N y , enters the nanometer regime. 9 In this thickness range, the increase in direct tunneling current through the gate oxide raises power consumption and device reliability issues.…”
mentioning
confidence: 99%